Puspin paradise a community-wide cat sanctuary in the urban landscape of Bonifacio Global City - Yukdawan, Alyssa Jade A.; Navarra, Nappy L.; Rosell, Auriga Joy B. (Quezon City College of Architecture, University of the Philippines Diliman, 2021)
Aside from humans, stray cats are also essential dwellers of the urban jungle. However, most urban cities are not designed with the consideration of the biological and behavioral needs of these non-human users, which forces the naturally well-mannered Puspins to become unruly scavengers, who scramble through garbage dumps in search of food and aggressively protect their small grimy homes. This study will come up with three urban landscape planning scenarios with varying degrees of cat requirement integration, assess and analyze which amongst these are the most ideal for Bonifacio Global City, and come up with guidelines and policies for this final scheme. This goal can be achieved with the use of the Human-Animal-Environmental Interrelationship Concept, Graph Theory, and Animal-Aided Design.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Cat sanctuary; Urban landscape architecture